2010
DOI: 10.1002/jmri.22209
|View full text |Cite
|
Sign up to set email alerts
|

In vivo vascular hallmarks of diffuse leukoaraiosis

Abstract: Purpose To characterize multiple patterns of vascular changes in leukoaraiosis using in vivo magnetic resonance imaging (MRI) techniques. Materials and Methods We measured cerebral blood flow (CBF), cerebrovascular reactivity (CVR), and blood–brain-barrier (BBB) leakage in a group of 33 elderly subjects (age: 72.3 ± 6.8 years, 17 males, 16 females). Leukoaraiosis brain regions were identified in each subject using fluid-attenuated inversion-recovery (FLAIR) MRI. Vascular parameters in the leukoaraiosis regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
46
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 55 publications
13
46
1
Order By: Relevance
“…These results are similar to findings from a previous study by Uh et al 22 reporting lower CVR values in leukoaraiosis. However, the approach to CVR quantification in the present study is more accurate.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These results are similar to findings from a previous study by Uh et al 22 reporting lower CVR values in leukoaraiosis. However, the approach to CVR quantification in the present study is more accurate.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are consistent with those in other studies reporting CBF reductions in leukoaraiosis compared with NAWM, 22,[45][46][47] but they are not in agreement for CBV. We found a reduction in CBV, possibly due to a loss of vascular density, whereas another study showed no difference in CBV between leukoaraiosis and NAWM.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Originally noted as diffuse, non-specific subcortical white matter lesions on CT, leukoaraiosis (LA) is a common finding among patients with ischemic stroke and has been associated with poor post-stroke outcomes as well as increased risk for recombinant tissue plasminogen activator (rtPA)-associated intracranial hemorrhage [4,5,6,7]. LA has been associated with reduced brain perfusion and cerebrovascular reactivity and may therefore considerably decrease penumbral survival and negatively affect outcome [8,9]. Yet, contribution of LA to outcome in stroke patients with ILAO remains to be clarified.…”
Section: Introductionmentioning
confidence: 99%